The influence of the China GLIM standards on the diagnosis of malnutrition in patients with hematopoietic stem cell transplant - Guo, Feng; Min, Liu; Chengyuan, Li; Hong, Liu; Meng, Wang; Chenyi, Tang; Jinru, Wu; Wei, Wu; Hua, Liu (Frontiers in Nutrition, 2023)
Background The muscle-related indicator is removed from Global Leadership Initiative on Malnutrition (GLIM) criteria implemented in China for many reasons. Patients with hematopoietic stem cell transplants are at nutrition risk and can enter into the second step of GLIM; thus, they are suitable for learning the diagnosing malnutrition significance between primary GLIM and GLIM-China criteria. This article aims to explore the role of muscle mass in the diagnostic criteria of malnutrition and the effects of GLIM-China for diagnosing malnutrition. Methods A total of 98 inpatients with hematopoietic stem cell transplants (HSCT) were recruited. Nutrition risk was assessed by using the Nutritional Risk Screening 2002 (NRS-2002). Appendicular skeletal muscle mass (ASMI) and fat-free mass index (FFMI) were determined using the bioelectrical impedance analysis (BIA) method. Malnutrition is defined by GLIM-China, GLIM, and PG-SGA. We use erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) to assess inflammation in GLIM and GLIM-China. The correlation or consistency among ASMI, FFMI, ESR, CRP, GLIM-China, GLIM, and PG-SGA was evaluated, respectively. Results One hundred percent instead of the patients had nutritional risk. The magnitude of malnutrition using PG-SGA, GLIM, and GLIM-China was 75.5, 80.6, and 64.3%, respectively. GLIM-China and PG-SGA showed the same performance (p = 0.052 vs. 1.00) and agreement (kappa = 0.404 vs. 0.433, p < 0.0001) with the FFMI. Consistency was noted between ASMI and PG-SGA in the assessment of malnutrition (p = 0.664) with a good agreement (kappa = 0.562, p = 0.084). ASMI and FFMI could determine muscle mass reduction, which could not be determined by BMI, albumin (ALB), and pre-albumin (pre-ALB); 34% of GLIM-China (–) patients were with low ASMI, and 40% with low FFMI; 30.0% of patients with PG-SGA (<4) still have low ASMI, and 38.2% have low FFMI. Conclusion If only the PG-SGA scale is used as a diagnostic criterion for evaluating malnutrition, a large proportion of patients with reduced muscle mass will be missed, but more patients with muscle loss will be missed via GLIM-China. Muscle-related indicators will help diagnose malnutrition.